Fakta Kemanusiaan dan Subjek Kolektif dalam Film The Journey: Cerminan Struktur Sosial dalam Anime - Nurhasanah, Aviah; Rohanda, Rohanda; Dayudin, Dayudin (Universitas Al Azhar Indonesia, 2025)
The presence of anime, in addition to functioning as entertainment, often also reflects social structures through depictions of human reality and social identity, one of which is the anime The Journey. This anime presents a story in the context of Middle Eastern history and culture. This study aims to reveal how human facts and collective subjects are represented as a reflection of social structures in Anime. The research data are in the form of scenes, dialogues, and storylines of the anime film The Journey which was released in June 2021. The data collection technique was carried out using the listening and note taking technique. The results and discussion show that the anime The Journey depicts human facts and collective subjects Arab society through the social structure in the film. Through the genetic structuralism, prove that social structures in anime is not only fictional, but also a reflection of Arab society. This finding supports Lucien Goldmann's theory that literary works and popular culture can reflect social group. This study only focuses on two basic concepts of genetic structuralism, human facts and collective subjects. It is hoped that further research can continue research either with the same or different theories.Keywords – Collective Subject, Genetic Structuralism, Human Facts.